2005
DOI: 10.1093/rheumatology/keh697
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 12 (IL12B), interleukin 12 receptor (IL12RB1) and interleukin 23 (IL23A) gene polymorphism in systemic lupus erythematosus

Abstract: These results suggest that polymorphisms located in IL12B, IL12RB1 and IL23A genes may not play a relevant role in the susceptibility or severity of SLE in the Spanish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 28 publications
4
26
1
Order By: Relevance
“…Our present results are different from findings in other population showing lack of association of IL12Bpro polymorphisms with SLE incidence [18]. Possible explanations of this discrepancy could be the variety of the genetic contributions in different ethnicities derived from different ancestral groups, as well as the gene interactions between IL12B polymorphisms and other loci.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our present results are different from findings in other population showing lack of association of IL12Bpro polymorphisms with SLE incidence [18]. Possible explanations of this discrepancy could be the variety of the genetic contributions in different ethnicities derived from different ancestral groups, as well as the gene interactions between IL12B polymorphisms and other loci.…”
Section: Discussioncontrasting
confidence: 99%
“…However, no significant associations between other investigated polymorphism in cis-regulatory region of IL12B gene, a substitution of A to C at position ?16,974 in 3 0 UTR, and SLE were observed. Previous study had shown that both polymorphisms in IL12B may not play a relevant role in the susceptibility or disease expression of SLE in the Spanish population [18]. Recently, a weak association was observed between A-allele of SNP in 3 0 UTR of IL12B gene in SLE patients with proteinuria among Thais population [19].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Besides, the combination of the IL-12B rs17860508 GC allele and/or IL-12B rs3212227 C allele increased the risk of SLE and/or the severity of SLE parameters in Polish population [45]. Other studies have showed that C allele in IL-12B 3′ UTR connected with higher production of IL-12p70 while GC allele in IL-12B promoter binding with Sp1 increased gene transcription and cytokine activity [46][47][48][49][50][51][52]. All these alleles might increase the levels of IL-12 and affect the immune response via regulation of T cell activity, resulting in abnormalities in SLE.…”
Section: Il-12 and Its Regulatory Roles In Slementioning
confidence: 98%
“…Past studies have revealed that synthetic oligodeoxynucletides (ODN) with TTAGGG motif, which highly accumulated in telemeric region of mammalian chromosomes, could be suppressed to treat autoimmune disease [50][51][52]. Sano et al reported that ODN without CpG motifs functioned as an adjuvant to induce Th2 differentiation and Dong et al reported that glomerulonephritis and survival of lupus mice model were improved by synthetic ODN with significant reduction of anti-ds DNA auto-antibody, IL-12, IFN-γ and IL-6.…”
Section: Il-12 and Ifn-γ Targeted Therapy For Slementioning
confidence: 99%